Efektivitas Terapi Applied Behavior Analysis (ABA) terhadap Perkembangan Bahasa pada Balita Usia 1-2 Tahun dengan Keterlambatan Bicara - Devi Theda Rizaldy Putri; Retno Setyo Iswati; Annah Hubaedah; Nina Hidayatunnikmah (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Speech delay is one of the most common developmental disorders in toddlers, potentially affecting communication and social skills. The age of 1–2 years is a golden period of brain development, where appropriate language stimulation is crucial. This study aimed to determine the effectiveness of Applied Behavior Analysis (ABA) therapy on language development in toddlers aged 1–2 years with speech delay. A pre-experimental design was used with one group pre-test and post-test. The sampling technique applied was total sampling, involving 15 toddlers at Rumah Terapi Ridha Sidoarjo. Language development was assessed using the Capute Scales. ABA therapy was administered weekly over 8 weeks, involving structured activities such as vowel recognition, syllable repetition, and word formation. Prior to intervention, all participants (100%) were categorized as poor, with an average score of 67.17. After therapy, 40% of children moved to the fair category, with an average score of 79.82. The Shapiro-Wilk test confirmed normal data distribution, and the paired t-test showed a significant difference (p = 0.001). These findings indicate that ABA therapy significantly improves language development in toddlers with speech delay and may serve as a practical intervention for early language support.